Improving the Efficiency and Sustainability of Oil Palm Plantations through Organic Fertilizer from Palm Oil Mill Waste - Martial, Tri; Lubis, Yusniar; Harefa, Taslim (Universitas Panji Sakti, 2024)
The sustainable management of palm oil plantations poses significant challenges, particularly in ensuring long-term efficiency and environmental sustainability. This study explores the impact of using Palm Oil Mill (PKS) waste as an organic fertilizer on enhancing the management efficiency of palm oil plantations. Using Data Envelopment Analysis (DEA), we evaluated plantation management efficiency at PT. Padasa Enam Utama over the period 2020-2023. Strengths of the Data Envelopment Analysis model include its objectivity and capacity to rate efficiency using numerical data rather than subjective opinions. The input variables included labor costs, fertilizer use, and land area, while output variables encompassed productivity and financial profits. Results reveal that average efficiency in 2020 was 0.85, categorizing it as “inefficient.” By 2021, efficiency improved to 0.92, achieving a “moderately efficient” status, and further rose to 0.95 in 2022, reaching “efficient” status. In 2023, efficiency slightly decreased to 0.94, though it remained within the efficient range. Findings suggest that PKS waste application significantly enhances plantation management efficiency, particularly through optimizing input and output variables. Additionally, employing PKS waste as organic fertilizer provides an eco-friendly alternative that reduces dependency on chemical fertilizers, contributing to sustainable farming practices. Research implications can contribute to supporting policies on the utilization of PKS waste to support more sustainable oil palm plantations.